FACTOR ANALYSIS ON LAYANAN SYARIAH LINKAJA USAGE DECISION - Nisrina Nur Azizah; Fuad Mas'ud (JURNAL STUDI MANAJEMEN ORGANISASI, 2021)
In the midst of intense e-wallet competition and seeing the large Muslim population, PT Finarya innovated to issue Layanan Syariah LinkAja which makes it unique as the first and only sharia e-wallet in Indonesia. This study aims to determine the effect of perceived ease of use, perceived usefulness, trust and riba knowledge towards Layanan Syariah LinkAja usage decision. The data collection method was done through questionnaire. The population in this study is Layanan Syariah LinkAja Muslim users in Indonesia. The exact population is unknown, so researcher took a sample of 100 respondents with purposive sampling approach. The analysis technique used is multiple linear regression analysis which is calculated using SPSS 26 program. The result of the analysis showed that perceived usefulness, trust and riba knowledge variables have a positive and significant effect on usage decision, while perceived ease of use variable has no effect on usage decision. Simultaneously, the results of the independent variable which are perceived ease of use, perceived usefulness, trust and riba knowledge have an effect on usage decision.